1997
DOI: 10.1098/rsta.1997.0101
|View full text |Cite
|
Sign up to set email alerts
|

Modelling plastic zones and the brittle-ductile transition

Abstract: Many crystalline solids fail by cleavage at low temperatures and by plastic processes at high temperatures. In the transition region, cleavage failure occurs at stresses increasing with increasing temperature, reflecting a decrease in yield stress and a consequent increase of plasticity around the crack tip. Crack tip plasticity blunts the crack and shields it through the compressive stresses in the plastic zone. This competition between cleavage and plastic flow can be modelled in terms of the generation (fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Experimental studies on these materials have shown that the T BDT / strain rate behaviour follows an Arrhenius law with an activation energy equal to that for dislocation glide [2,5]. Dislocation-dynamics models of slip around crack tips and the elastic "shielding" of the crack tip by the active dislocations fit the experimental results to high accuracy [6]. In other materials such as TiAl [7], NiAl [8] and zirconia [9], an Arrhenius law for the BDT with a well-defined activation energy is found, but no data exist for comparison with the thermal activation parameters of dislocation glide.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Experimental studies on these materials have shown that the T BDT / strain rate behaviour follows an Arrhenius law with an activation energy equal to that for dislocation glide [2,5]. Dislocation-dynamics models of slip around crack tips and the elastic "shielding" of the crack tip by the active dislocations fit the experimental results to high accuracy [6]. In other materials such as TiAl [7], NiAl [8] and zirconia [9], an Arrhenius law for the BDT with a well-defined activation energy is found, but no data exist for comparison with the thermal activation parameters of dislocation glide.…”
Section: Introductionmentioning
confidence: 75%
“…The dislocation velocity / stress / temperature relation for a given material is a key input parameter for dislocation dynamics modelling of the BDT [6,23]. Currently the only dislocation velocity data available for tungsten are at room temperature and 77K [15], and thus derivation of a sound dislocation velocity law for the experimental temperature range used here is problematic.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is called ''shielding effect'' due to dislocations. 28) summarised the BDT temperature of single crystal silicon from several groups and plotted ln(strain rate), ln _ " ", against reciprocal BDT temperature, 1=T BDT , showing that each line from the collected data exhibits the same angle of slopes in the ln _ " " -1=T BDT diagram but shows different interceptions of the lines with the axis of ln _ " ". This indicates that the activation energy for the BDT is constant over the whole results used, being independent from the shape or measure of the experiment, however, the BDT temperature depends on the way of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon crystals have been employed as a model substance to understand such dislocation process, since highly perfect crystals are obtainable and they exhibit a very sharp BDT. 1,2) When the BDT occurs to cause a steep increase of fracture toughness, a burst of dislocation multiplication takes place around the crack tip. However, TEM studies for such dislocation process in Si have been very limited so that the mechanism of the sharp BDT has been still unclear from the viewpoint of the dislocation theory.…”
Section: Introductionmentioning
confidence: 99%